Theory driving research : new wave perspectives on self-processes and human development - McInerney, D. M.; Marsh, Herbert W.; Craven, Rhonda G.; Guay, Frédéric (International advances in self research., 2013)
Theory Driving Research: New wave perspectives on self-processes and human development provides a unique insight into self-processes from varied theoretical perspectives. The chapters in this volume develop avant-garde theoretical ideas to drive future, cutting-edge, empirical research and together, in one collected volume, make a valuable contribution to scholarly literature on self-processes. Among the themes covered are resurrecting the "I-self", a re-look at the dichotomy between the I-self, and the Me-self based on James's analysis, the actualization of human potential, naturalizing and contextualizing the self, hypo-egoic states, personal proficiency networks, competition and performance relationships, achievement motivations, passion and optimal functioning in society, competence and self-worth threat, new interpretations of expectancy-value research, methodological advances in BFLPE research and multilevel models of student achievement motivation. This monograph, the fourth in the International Advances in Self Research monograph series, provides wealth of information on new theorizing and provides a platform for generating the next wave of research designed to understand the fundamental role self-processes play in human development.